PENGEMBANGAN MEDIA PEMBELAJARAN STEP BOX “TAMAM” UNTUK KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS I SDN BERENG MALAKA - Dehen Kampili; Nurul Hikmsh Kartini; Esti Aryani Safithry (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop, assess the feasibility, and test the effectiveness of the Step Box “TAMAM” (Tau Mambasa) learning media in improving the early reading skills of first-grade elementary school students. The media was developed using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The results of the needs analysis indicate that students experience difficulties in early reading due to the limited availability of engaging, interactive media that aligns with the stages of early literacy development. The Step Box “TAMAM” media was designed in four levels—letters, syllables, words, and sentences—to facilitate structured, multisensory learning. Validation by language experts and media experts showed that the media is highly feasible, with high ratings in material quality, language use, visual appearance, and ease of use. Effectiveness testing using a pretest–posttest design demonstrated a significant improvement in students’ reading abilities, with an average N-Gain of 0.739 (high category). All students showed improvement, with 35.7% falling into the high category and 64.3% into the medium category. Thus, the Step Box “TAMAM” media is effective, engaging, and can serve as an innovative alternative for early reading instruction in elementary schools